2020
DOI: 10.3390/molecules25163758
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Characterisation and Antihypertensive Effects of Locular Gel and Serum of Lycopersicum esculentum L. var. “Camone” Tomato in Spontaneously Hypertensive Rats

Abstract: Blood pressure control in hypertensive subjects calls for changes in lifestyle, especially diet. Tomato is widely consumed and rich in healthy components (i.e., carotenoids, vitamins and polyphenols). The aim of this study was to evaluate the chemical composition and antihypertensive effects of locular gel reconstituted in serum of green tomatoes of “Camone” variety. Tomato serum and locular gel were chemically characterised. The antihypertensive effects of the locular gel in serum, pure tomatine, and captopri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 56 publications
2
20
0
Order By: Relevance
“…Previous experiments performed in our laboratory, as well as studies by other researchers [4,23], have confirmed that the levels of locomotor and searching activities are higher in SHRs than in WKY rats. Interestingly, an attenuation of locomotor hyperactivity, as determined by a significant decrease in locomotion, was observed in SHRs receiving tomato Gs, tomatine and captopril with respect to SHRs receiving vehicle.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Previous experiments performed in our laboratory, as well as studies by other researchers [4,23], have confirmed that the levels of locomotor and searching activities are higher in SHRs than in WKY rats. Interestingly, an attenuation of locomotor hyperactivity, as determined by a significant decrease in locomotion, was observed in SHRs receiving tomato Gs, tomatine and captopril with respect to SHRs receiving vehicle.…”
Section: Discussionsupporting
confidence: 79%
“…Previous studies have shown that Camone tomato fraction (the locular gel surrounding the seeds and the serum, normally discarded during industrial processing of tomato concentrate, tomato pulp and tomato sauce) is rich in bioactive compounds [3,4] such as the glycoalkaloid tomatine and chlorogenic and caffeic acids, important biologically active dietary polyphenols. Although it differs in chemical components from red tomatoes, the Camone variety has a higher antioxidant capacity [3,4]. Some authors have reported that the consumption of natural polyphenols results in an improvement of cognitive functions [22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although not always explicitly recognized in studies, five used simple gf mutants [67,71,78,127,130], one a gf gs combination [93], and one a couple of green-fruited genotypes that were supposedly due to the combination of gf and r [71].…”
Section: Use Of "Special" Tomato Genotypes As a Testermentioning
confidence: 99%
“…It is now well known that glycoalkaloids also possess beneficial effects for human health [ 6 , 8 , 9 , 10 ], as well as many other secondary metabolites [ 11 , 12 , 13 , 14 , 15 , 16 ]. Thus, rapid methods for the quantification of α-tomatine and dehydrotomatine in tomato fruits are potentially useful.…”
Section: Introductionmentioning
confidence: 99%